Diurnal Variation of Carbon Dioxide Flux Over Rice Paddy - Islam, MA; Mano, M; Hossen, MS; Miyata, A; Baten, MA (Journal of Environmental Science and Natural Resources, 2017)
An experiment was conducted to measure carbon dioxide (CO2) flux by using the eddy covariance technique over rice paddy field at Mymensingh flux study site at Bangladesh Agricultural University, Mymensingh at three growing stage in Aman season in 2015. The variation of CO2 flux in the experimental period displayed distinct diurnal variations as influenced by rice growth and development. The diurnal pattern of CO2 flux showed broad peak at flowering stage of Aman rice at DOY 285 due to photosynthesis. The diurnal pattern of CO2 flux showed also higher broad peak at 1500 hour in DOY 272 at vegetative stage and lower broad peak at 1300 hour in DOY 330 ripening stage of Aman rice due to photosynthesis, meteorological conditions and field management activities. J. Environ. Sci. & Natural Resources, 9(2): 127-130 2016